MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS MELALUI PENERAPAN REWARD AND PUNISHMENT DI SMA NEGERI 1 GLUMPANG TIGA - Faisal Rizal (Jurnal Real Riset, 2022)
Improving the quality of learning in schools is highly dependent on several factors. A very important factor, among others, is the application of school culture towards quality improvement. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of discipline, including the discipline of teachers in class attendance in the teaching and learning process. To improve the discipline of teachers can be pursued in various ways. In this School Action Research (PTS), an action was tried in the form of implementing Reward and Punishment for teachers at SMA Negeri 1 Glumpang Tiga, Pidie District, Aceh Province. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, teacher discipline in class attendance in the teaching and learning process increased and met the predetermined indicators of 80%. In Cycle I there were 10 teachers who attended less than 10 minutes or 21.27%, 16 people or 354.04% teachers who attended 10 to 15 minutes, while 21 people or 44.68 teachers who attended more than 15 minutes %. After conducting data analysis and coaching as well as panishment and reward and improvement, then proceed to cycle II with the following results. There are 42 teachers who attend less than 10 minutes or 89.36%, 5 people or 10.63% of teachers who are present between 10 to 15 minutes or 4,25%. Thus, in the second cycle the teacher's attendance has exceeded the attendance standard of 80%. From the results of this study, it can be concluded that to improve teacher discipline in class attendance in teaching and learning activities can be done by applying Reward and Punishment to teachers.Keywords: Teacher Discipline, Reward and Punishment